Correction of impairments of visceral blood flow and oxygen-carrying function of the portal blood in diffuse purulent peritonitis - B. M. Belik; V. A. Suyarko; D. V. Mareev; S. Yu. Efanov; K. G. Pyasetskiy (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The authors assessed an efficacy of correction of visceral blood flow and oxygen-carrying function of portal blood in patients with diffuse purulent peritonitis. The intraportal infusion therapy was applied using ozone-saturated solutions. MATERIAL AND METHODS. There were investigated the dynamics of index changes in blood flow of the portal vein, common hepatic artery, superior mesenteric artery and main parameters of oxygenation of system and portal blood. RESULTS. There was found that the application of intraportal infusion therapy facilitated to hepatic and mesenteric blood flow, oxygen-carrying function of portal blood and liver oxygenation. The method helped to restore liver function and eliminated enteral disfunction and it decreased severity of patients’ state that allowed doctors to improve treatment outcomes. CONCLUSIONS. The intraportal infusion therapy using ozone-saturated solutions is an important part of treatment management in severe forms of purulent peritonitis.